The underwater photographer - Edge, Martin. (Focal Press, 1996)
"The Underwater Photographer is a third edition, but it has been so thoroughly revised to include digital techniques that it could have easily justified a new title...The Underwater Photographer is seriously comprehensive and will clearly serve as a faithful reference manual. But the author's enthusiastic, personal and accessible style make it easy reading. Technical issues are dealt with thoroughly but reassuringly free from jargon, and even if it gets a bit technical, you can always skim through the heavy stuff and skip to Martin's personal recommendations, to instantly improve your shots...In conclusion, this book is very impressive and as up to date as a work of this magnitude could hope to be. In short, if you are an underwater photographer and want to improve your images then I recommend buying this book" - Alex Mustard, www.wetpixel.com